The Effect of Pressure on Superconducting Copper Mixed Oxides - Marezio, Massimo; Chenavas, Jean (Journal of solid state chemistry, 1996)
This article comprises four sections. The first introduces the subject of pressure-induced syntheses and phase transitions taking place in ionic compounds. Examples are described to illustrate the general trends governing these transformations, namely the increase of the cation and anion coordinations under pressure and the greater compressibility of anions with respect to that of cations. In the second section, pressure-induced phase transitions taking place in superconducting layered cuprates are discussed and the only example known so far, that occurring inACuO2compounds, is illustrated. In the third section, pressure-induced syntheses are discussed. The examples in which pressure has been crucial to obtain new phases are numerous. In some cases, like the Hg-based cuprates, the new compounds are not high pressure phases, but nevertheless the use of pressure has greatly helped to optimize the synthesis of the samples. In other cases, like Sr2CuO3+δ, only the synthesis under pressure yields superconducting samples. In the fourth section, thein situpressure studies carried out at Houston, Grenoble, Birmingham, and Argonne are described. The dramatic increases ofTcfor the first four members of the Hg homologous series are strictly correlated to the shortening of the apical Cu–O distance which in these compounds is anomalously large at ambient pressure. If the structural arrangement responsible for 164 K superconductivity has to be stabilized by substitution, second nearest-neighbor interactions must be taken into account. The synthesis of such compounds should be one of the primary future goals.